MENINGKATKAN HASIL BELAJAR SENI BUDAYA DAN KETERAMPILAN MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) SISWA KELAS VI SDN SUKOREJO 1 KECAMATAN REJOSO KABUPATEN NGANJUK - Istikakimi Istikakimi; Wiwik Retno Astuti (Jurnal Muassis Pendidikan Dasar, 2022)
The purpose of this study is to improve the learning outcomes of arts and culture using a project based learning (PJBL) model for sixth grade students at SDN Sukorejo, Rejoso District, Nganjuk Regency. Where this research is a classroom action research which consists of two cycles. Where each cycle includes several stages ranging from planning, implementation, observation, and reflection. The subjects of this study were 19 grade VI students with details of 8 male students and 11 female students. Data obtained from the results of observations, tests, and documentation. Data were analyzed qualitatively and quantitatively with a percentage of completeness of 80%. The results showed that the average value in cycle 1 was 76.74 with details of students who completed as many as 4 and students who had not completed as many as 15 with an achievement percentage of 21.05%. Furthermore, in cycle 2, the average student score was 85.74 with details of students who completed as many as 16 and students who had not completed as many as 2 with an achievement percentage of 84.21%. Based on these results, it can be said that the classical value has been achieved, which is more than 80% in cycle 2. Based on these results, it can be concluded that the project based learning model can be used as an alternative to improve student learning outcomes, especially in learning arts and culture and skills